Polarization dependence of intraband absorption in self-organized quantum dots - Chua, S. J. (2013)
Photoluminescence and intraband absorption were investigated in n-doped self-organized InAs and In0.35Ga0.65As quantum dots grown on a GaAs substrate. Intraband absorption of the dots is strongly polarized along the growth axis in the mid infrared spectral range. The absorption is maximum at around 120 meV for InAs dots and at 130 meV for In0.35Ga0.65As dots. The experimental results on InAs dots are in agreement with published theoretical calculations.